THE ROLE OF AGRICULTURAL EXTENSION AGENT AND ANALYSIS OF BUSINESS MODEL CANVAS IN IMPROVING SMALLHOLDER TEA INDUSTRY OF FARMERS GROUP IN MARGAMULYA VILLAGE AND CISONDARI VILLAGE, PASIR JAMBU SUB-DISTRICT, BANDUNG REGENCY - Nurgraha, Rd. Much. Jusup (Jurnal Aplikasi Manajemen, 2017)
This research is located in the community plantation of Margamulya village and Cisondari Village, Pasirjambu District Bandung Regency is one of export quality tea producer. The purpose of this research is to analyze the role of extension worker and knowledge of canvas business model analysis (MBC) in an effort to increase the business of Tani Teh Rakyat group by using descriptive and verification research method. The result of the research shows that t-test of agricultural extension performance (X1) tcount (6,234)> ttable (1,675), while MBC (X2) tcount (1,777)> ttable (1,675), X1 and X2 have significant effect to business group peasant tea (Y). Ftest results obtained Fcount> Ftabel is 19.542> 3.18. With the limitations of this study, further research is needed to assess the development of competence of agriculture extension agents and farmers improvement strategies, especially for areas that are still weak in assistance.